Analisis Pengaruh Bio Additive Pada Bahan Bakar Terhadap Unjuk Kerja Mesin 4 Langkah - Poppy Aprilya Sitorus; Rahmatullah Rahmatullah; Darianto Darianto; Muhammad Idris (JOURNAL OF MECHANICAL ENGINEERING MANUFACTURES MATERIALS AND ENERGY, 2022)
Bioadditives are elements derived from plants that are used as additives to improve fuel quality. Citronella oil is one type of essential oil that has been studied for its potential as a fuel bio additive because of its volatility and ability to dissolve into fuel. The purpose of using this bioadditive is to increase engine performance. This research was conducted using an experimental method, some of the samples tested consisted of pertalite fuel, bioethanol then the development was carried out by adding the Bioadditive element citronella oil to the fuel with a ratio of 2,0 : 1000 ml, 3,0 : 1000 ml, and 3,5 : 1000 ml. The sample test was aimed to measure engine performance using a dynamometer. The results of this study show that the use of citronella bioadditives can improve motorcycle performance, the maximum power increases by 55% at a ratio of 2,0 : 1000 ml, and the optimum torque is achieved by 39% at a ratio of 2,0 : 1000 ml. In addition to these tests, measurement of fuel consumption is also carried out by producing a savings of 10%, using a ratio of 2,0 : 1000 ml.